Metode Peningkatan Literasi pada Pendidikan: Analisis Bibliometrik pada Publikasi 2013 – 2023 - Rasyid Zuhdi; Bagiya Bagiya; Suci Ika Febrianti (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
This study aims to determine the conditions in the range of 2013-2023 related to the scientific map, publication trends, and thematic research coverage of literacy learning methods in education, especially articles published in Scopus, Google Schoolar, and Crossref indexed journals. The research process focused on the following questions: (1). How are literacy improvement methods in education seen from the publication map; (2). What is of interest to academics regarding literacy improvement methods in education? and (3). What topics are often written about in publications related to methods of improving literacy in education? In addition to the research and data sources to be used in the bibliometric analysis, 1200 articles were found through the keywords